A Survey on Web Service Discovery Approaches - Mosa, Abdelghany (2021)
Mosa, A., & Abdelaziz, A. (2021). A Survey on Web Service Discovery Approaches. Fusion: Practice and Applications, 5(2), 62-69. https://doi.org/10.54216/FPA.050202